PENGARUH JENIS PUPUK TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS JAGUNG MANIS - Syafruddin Syafruddin; Nurhayati Nurhayati; Ratna Wati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
A research was conducted at Experimental Farm of Faculty of Agriculture, Syiah Kuala University in February – Mei 2011. The objectives of the research were to determine effect of kind of fertilizer on growth and yield of several sweet corn varieties and also to know interaction between both factors mentioned. The experiment was performed using a randomized complete block design (RCBD), 3 x 3 with 3 replications. There were two factors studied, namely kinds of fertilizer, consisting of 3 levels: organic fertilizer, NPK and liquid organic fertilizer NASA. The second factor was varieties consisting of 3 levels: Bonanza, Manise, and Jago F1. The results showed that kinds of fertilizer exerted highly significant effects on diameter of bottom stem at age 45 day after planting (DAP), number of leaves at 45 DAP, leaf length at age 30 and 45 DAP and exerted a significant effect on ear length without cornhusk. The highest growth and yield of sweet corn was found in NPK fertilizer treatment. Varieties of sweet corn exerted highly significant effects on plant height age 15 DAP, diameter of bottom stem at age 30 and 45 DAP, number of leaf at age 15 DAP, leaf width at age 15, 30, and 45 DAP and exerted significant effects on ear length without cornhusk, ear diameter without cornhusk, ear weight per bed with border plant, ear weight per bed without border plant, ear weight with cornhusk and plant height at age 30 and 40 DAP, diameter of bottom stem at age 15 DAP, number of leaf at age 45 DAP, leaf length at age 15 and 45 DAP. The highest of growth and yield was found at Variety Bonanza. Additionally, there was no interaction between kinsd of fertilizer and several varieties of sweet corn on growth and yield of all variables observed.